The Creation of Contemporary Batik Motif Retak Seribu as an Innovation of the Remekan Technique for Traditional Batik Motifs - Basuki Sumartono; Adam Wahida (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Batik is one of the identities of Indonesian cultural products that is well known by the world community. Research on batik never runs out to be studied. The point of view of the study can be done from various disciplines. Although in terms of motifs, it has been researched many times, and it is possible to identify that the number of batik motifs in Indonesia can reach thousands of existing motifs, from traditional motifs to modern motifs. Kenneth F. Bates (in Riyanto, et al 1997: 15) reveals that what forms a physical motif are the spot elements (in the form of strokes, colors, textures) line (lines) and mass (mass / in the form of Figures) in a single unit. Then the motif is duplicated or given variations with repetition to form a pattern or field. In contrast to Adi Kusrianto (2013: 3) states that classical batik motifs have meaning for the Javanese. Classical batik ornaments must also be able to give birth to a harmonious sense of beauty between the composition of the color scheme and the arrangement of the ornaments. Greg Richards and Julie Wilson wrote that innovation is the introduction of new inventions or spreading the meaning of these new inventions into general use in society (Richards and Wilson, 2007: 6). This study aims to develop the technique and manufacture of retak seribu motifs originating from the remekan batik technique, the consideration being to simplify the manufacturing process and enrich the development of contemporary batik motifs in Indonesia. Thus, this research will use researchbased development with the following steps: 1) information collecting, 2) develop a preliminary form of product, 3) preliminary product testing, 4) main product revision, 5) main field testing, and 6) dissemination.